RNA-seq analysis of blood from cave- and surface-dwelling Astyanax morphs reveal diverse transcriptomic responses to normoxic rearing - Boggs, Tyler E.; Bucher, Lydia R.; Gross, Joshua B. (Frontiers in Physiology, 2025)
Adaptive responses to hypoxia are likely accompanied by highly diverse changes in gene expression. Here, we examined the transcriptomic regulation in blood samples derived from independently-derived captive cave-dwelling fish. These fish are members of the species Astyanax mexicanus, which comprises two morphs: an obligate subterranean form, and a “surface-dwelling” form that lives in rivers and streams located near cave localities. These morphs diverged ∼20,000–200,000 years ago, and cavefish derived from multiple, distinct cave localities have adapted to life in hypoxic waters. Here, we focused on captive-reared Astyanax morphs since elevated hemoglobin levels persist in cavefish despite rearing in the normoxic conditions of a laboratory. A GO enrichment analysis revealed several instances of convergent gene regulation between some, but not all, cavefish populations. This finding suggests that different gene expression patterns have evolved in response to hypoxia across geologically-distinct cave localities. Additionally, we identified differential regulation of numerous genes of the canonical hypoxic response pathway. Interestingly, some genes activating this pathway were expressed lower in captive-reared cavefish. These patterns of gene expression may have evolved in cavefish as a consequence of negative pleiotropic consequences associated with prolonged hif gene expression. At present, it is unknown whether this finding is a function of captivity, or whether these expression patterns are also present in wild populations. Collectively, this work provides new insights to the transcriptomic regulation of hypoxia tolerance using a cavefish model evolving in distinct oxygenated environments.